Eidos: Telos, Kammer/Kammer e altri balletti di William Forsythe - Siegmund, Gerald (Kritik. Rivista di letteratura e critica culturale, 2024)
This essay aims to illustrate the particularity of Forsythe’s projects and ballets. Among the relevant features of his ballets is the use of all the means of theater to create an autonomous scenic universe. Lights, space, music, text, costumes as well as bodies and their movements are understood as autonomous systems that on stage can enter into multiple connections to generate an openness that suspends and transforms the usual modes of perception and signification.